Art Therapy (Drawing) As A Medium for Emotion Revelation In Paranoid Schizophrenia Patients in Surabaya Hospital - Prima, Prima Permatasari; Akta Ririn Aristawati (Kirana Publisher (KNPub), 2025)
This research is an observation of a late adult who experiences paranoid schizophrenia. A person experiencing paranoid schizophrenia is less able to express their feelings. The purpose of this study is to assist clients in understanding their feelings, thoughts, and behaviors, can control their emotions, so that others and the surrounding environment can understand clients. This research uses an experimental design in the form of single-subject research with an A-B-A design. The data collection technique used in this research is by measuring behavior with data analysis using graphical techniques. The results show that the Art Therapy technique provided is quite successful, so it can help clients manage their emotions more healthily.